Penerapan Model Pembelajaran Student Facilitator and Eplaining untuk Meningkatkan Hasil Belajar Siswa Sekolah Menengah Kejuruan - Rahayu, Mamik (Universitas Negeri Malang, 2019)
This study aims to describe the application of Student Facilitator and Explaining learning models in the Nusantara Awareness material to student learning outcomes. This study use classroom action research with two cycles. Data collection is done through observation, assessment of learning outcomes, and reflection. Data analysis uses interactive analysis and descriptive statistics. The application of the Student Facilitator and Explaining learning model uses three steps, i.e., the transmission of material, the formation of groups, and students (facilitators) explaining the material to other students. The analysis shows that the psychomotor learning outcomes of students in the first cycle reached 80% with a good category. Psychomotor learning outcomes of students in the second cycle reached 83% or in the excellent category. The application of Student Facilitator and Explaining learning models can improve the learning outcomes of PPKn in vocational students..